2016
DOI: 10.1038/srep35808
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin 1’s Interaction with TC45 Attenuates Stat signaling by dephosphorylating Stat to inhibit antimicrobial peptide expression

Abstract: Impaired phosphatase activity leads to the persistent activation of signal transducers and activators of transcription (Stat). In mammals, Stat family members are often phosphorylated or dephosphorylated by the same enzymes. To date, only one Stat similar to mammalian Stat5a/b has been found in crustaceans and there have been few studies in Stat signal regulation in crustaceans. Here, we report that β-arrestin1 interacts with TC45 (45-kDa form of T cell protein tyrosine phosphatase) in the nucleus to attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Various antimicrobial peptide families such as penaeidins, crustins, ALFs, and stylicins have been identified in shrimp ( 49 , 63 ). In our previous study, we found that activation of the JAK/STAT pathway increased the expression of Alf-a1 , Alf-c1 , Alf-c2 , CrusI-1 , and CrusI-5 ( 64 ). The expression of Alf-c2 and CrusI-1 was regulated by the activation of Toll pathway ( 52 ).…”
Section: Discussionmentioning
confidence: 93%
“…Various antimicrobial peptide families such as penaeidins, crustins, ALFs, and stylicins have been identified in shrimp ( 49 , 63 ). In our previous study, we found that activation of the JAK/STAT pathway increased the expression of Alf-a1 , Alf-c1 , Alf-c2 , CrusI-1 , and CrusI-5 ( 64 ). The expression of Alf-c2 and CrusI-1 was regulated by the activation of Toll pathway ( 52 ).…”
Section: Discussionmentioning
confidence: 93%
“…42 Our results are consistent with reports showing that β-arr1 directly interacts with STAT1 in the nucleus following IFN- treatment, accelerates STAT1 dephosphorylation by recruiting tyrosine phosphatase (TC45) and consequently, negatively regulates the transcription of IFN--induced genes. 43,44 GPCRs undergo substantial fluctuations between active and inactive states.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been shown that iron oxide nanoparticles inhibit AMP function ( 85), what can be exploited for therapeutic purposes. b-arrestin1 was also shown to down regulate AMP expression in shrimp, by interacting with TC45, tyrosine phosphatase of T cells (86). Finally, it has also been reported that several cytokines are able to inhibit the expression of AMPs (87).…”
Section: Betrayal Of Host Defense Antimicrobial Peptides Amid Chaos: a Conflict In The Cell Membranementioning
confidence: 92%